The Impact of Artificial Intelligence in the Banking Sector in Nepal - Shrestha, Sajeeb Kumar; Mahat, Dipak (Academia Journal of Research and Innovation, 2025)
This study explores the effects of Artificial Intelligence (AI) on Nepal’s banking sector, focusing on its relationship with employee satisfaction, customer behavior, customer service, job obsolescence, and bank profitability. Utilizing a quantitative research design, data were gathered from 195 employees at four leading commercial banks in Nepal through convenience sampling, selected for its practicality and accessibility. The results demonstrate a significant positive correlation between AI implementation and employee satisfaction, customer behavior, and bank profitability. Conversely, the association between AI and customer service was found to be weaker, and no significant link was observed with job obsolescence. These findings offer strategic guidance for banks aiming to harness AI technologies effectively while addressing potential challenges, thereby contributing valuable insights for the sector’s ongoing digital transformation.